Enhancing Disaster Preparedness for Junior High School Students at SMPN 24 Padang City Using Virtual Reality Method - Boby Febri Krisdianto; Ilfa Khairina; Tiurmaida Simandalahi (Warta Pengabdian Andalas, 2024)
Indonesia frequently experiences earthquakes, resulting in significant financial losses and casualties, especially in Padang. A major factor contributing to the high number of victims is the general public's lack of knowledge and preparedness for such disasters. Teenagers, including middle school students, are particularly vulnerable. Consequently, at SMPN 24 in Padang, virtual reality (VR) technology has been introduced to educate students about disaster preparedness. This simulation provided a realistic learning experience, allowing students to practice for emergencies without endangering themselves. At SMPN 24 in Padang, 32 students underwent an earthquake simulation using the VR approach. The results indicated an enhanced understanding of disaster preparedness among the students, with the median comprehension score rising from 59.00 to 60.50. Evaluations suggest that VR technology effectively increases students' disaster awareness and readiness. In summary, thanks to the virtual reality (VR) training, students at SMPN 24 in Padang feel better equipped to face potential earthquake disasters.